Policies for wetlands implementation in Denmark and Sweden – historical lessons and emerging issues. (February 2021) - Graversgaard, Morten; Jacobsen, Brian H.; Hoffmann, Carl Christian; Dalgaard, Tommy; Odgaard, Mette Vestergaard; Kjaergaard, Charlotte; Powell, Neil; Strand, John A.; Feuerbach, Peter; Tonderski, Karin
Highlights: Historical comparison of wetland implementation provides learnings across countries Policy changes establish enabling and constraining factors for farmers' participation A narrow policy focus limits the potential for wetland implementation More advice and support to farmers are required to secure efficient wetlands Abstract: Natural wetlands used to cover a significant part of the landscape, but these ecosystems have declined by >50% worldwide, and even more in Denmark and Sweden. However, since the 1980s, various policies have been implemented to restore and create wetlands. This study provides a comprehensive historical overview of policies used to stimulate the creation and restoration of wetlands in Denmark and Sweden, and also analyses what factors have facilitated participation or have been barriers for landowners. The analysis of wetlands implementation programmes in Denmark showed a change towards narrower focus on nitrogen reduction from 1998 and onwards, whereas policies in Sweden often have had a wider multifunctional purpose. In both countries, there has been a change in the compensation structure from a lump sum to annual payments, parallel to an observed increase in costs for wetlands implementation. There is still a large potential for recreating many more wetlands, and the national targets have not been reached in neither Denmark nor Sweden. Key success factors, for future wetlands implementation are sufficient compensation levels, flexible scheme designs and information-based strategies documenting relevant benefits and sustainability issues. In general, more advice and support from the state, regional and local participants, and farmers' organisations, are required to increase the participation and achieve successful and cost-efficient wetlands implementation. A collaborative and catchment-based approach holds promise, where wetland governance can serve as a platform for collaboration between policy bodies and between farmers. Additionally, politicians and decision makers need to accept the area targets presented to them when setting policy goals for wetlands implementation, and to accept that restoring and constructing wetlands requires long implementation times before results can be demonstrated.